Finite Element Analysis of Elastomeric Push Fit Spigot and Socket Steel Pipe Joint - Abdul Aziz, Nuraini (2000)
Pipe is the most important medium, which supplied water from one place to another. For places, which are far from the reservoir, the pipes must be joined in order to get water supply. A good pipe joint technique or method can reduce the non -revenue water. Spigot and socket push - fit joint is one of the methods, which can be used for this purpose. This technique were mostly used for small diameter pipe but has not been introduced for steel main pipe. With the co-operation from BOON & CHEAH STEEL PIPES SDN.BHD. company, a project has been developed to analyse the ability of the joint for 600mm steel pipes. Finite element method was used to analyse the ability of this joint. Two types of finite element software were used namely, LS-OYNA30 and LUSAS1 3. Both software have different processing system but they have the ability to analyse rubber material. Elastomer, which was used in this' study, used Mooney-Rivlin strain energy equation. There were another two methods involved, theoretical and experimental methods, to support the finite element analysis of the joint. LS-DYNA3D software was used for the 2 dimensional plane stress and axisymmetry elastomer using compression method to determine the pressure distributions at the top and bottom surface of the elastomer. Changes of the elastomer thickness and width (t and h) values have been made for the plane elastomer to identify the suitable pressure distribution, which can withstand the water pressure in the pipe. As for the analysis using LUSAS1 3, the 2 dimensional axisymmetry elastomer was being pushed to determine the pushing force, which can be used for the pipe connection. From the theoretical, experimental and finite element analysis, it has been identified that the maximum pressure value at the top surface of the elastomer is higher than the water pressure in the pipe. The best pressure distribution developed was at t=3 mm and h=0.51mm. For the pushing force analysis, it is identified that to fit the joint, the pushing force must exceed 10 kN. From the result, it is shown that the joint method can be used for large size steel pipe because the pressure value developed was higher than the internal water pressure. For the ease of joining, it has also been identified that the pushing force must be higher than the shear stress produced by the elastomer. Some recommendations has been proposed to get the most benefit of the analysis.